Extracellular vesicles of follicular fluid from heat-stressed cows modify the gene expression of in vitro-matured oocytes - Dalanezi, Felipe Morales [UNESP]; Mogollon Garcia, Henry David [UNESP]; Ferrazza, Rodrigo de Andrade [UNESP]; Franchi, Fernanda Fagali [UNESP]; Fontes, Patricia Kubo [UNESP]; Souza Castilho, Anthony Cesar de [UNESP]; Gouveia Nogueira, Marcelo Fabio [UNESP]; Santos Schmidt, Elizabeth Moreira dos [UNESP]; Sartori, Roberto; Pinheiro Ferreira, Joao Carlos [UNESP] (Elsevier B.V., 2019)
The effect of heat stress (HS) on cattle reproduction is deleterious with respect to ovarian follicular development and oocyte quality. The objective of this study was to investigate the effect of follicular fluid extracellular vesicles (EVs) obtained from cows maintained in thermoneutral (TN) or HS conditions on in vitro oocyte maturation. Nonlactating cows were estrous synchronized. Immediately after ovulation day (D1), the cows were randomly assigned to TN or HS environments. Follicular fluid from all follicles from each treatment was pooled, and EVs were obtained. Pools of 20 cumulus oocyte-complexes (COCs), were allocated to the following treatments: Control (n = 4 COC pools): matured in base medium; TN (n = 4 COC pools): matured in base medium supplemented with TN EV suspension; and HS (n = 4 COC pools): matured in base medium that was supplemented with the HS EV suspension. All treatments were conducted at 38.5 degrees C for 24 h in a humid atmosphere with 5% CO2. After maturation, the COCs were evaluated for meiotic progression, DNA integrity and oocyte quality-related gene expression. When the experimental groups were compared with the control group, a treatment effect was not observed for meiotic progression and DNA integrity. In the cumulus cells of TN group, there was relatively lesser expression of the IGFBP4 gene. In the oocytes of the TN as compared with the HS group, the IGFBP2, BMP15, GDF9, CDCAS, HAS2, RPL15, STAT3 and PFKP genes were expressed to a lesser extent. The findings indicated that oocytes matured in the presence of EVs from the follicular fluid of cows collected when there were TN conditions, however, there was a lesser expression of genes related to oocyte quality.
Keywords: Dairy; Reproduction; Biotechnology; Exosomes